Declining Contribution of Plant Physiological Effects to Global Drought Characteristics With Rising CO2 Using State‐of‐the‐Art Earth System Models - Ziwei Li; Fubao Sun; Hong Wang; Tingting Wang (Earth's Future, 2025)
Abstract Vegetation physiology responses to rising atmospheric CO2 can alter the global hydrological cycle, thereby influencing drought occurrence. It has long been controversial and poorly understood how vegetation physiological effects influence meteorological drought characteristics with increasing CO2. To investigate that, we employ multiple CO2 sensitivity experiments of the state‐of‐the‐art Earth System Models (ESMs) in the Coupled Model Intercomparison Project Phase 6 (CMIP6). We quantify drought characteristics in response to rising CO2 using two drought indices: the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI), with SPEI calculated using both the Penman‐Monteith method (SPEI_PM) and energy‐only method (SPEI_Rn). Our findings reveal that plant physiological effects can robustly induce more intense, frequent, and prolonged droughts under elevated CO2 levels. Spatially, drought intensity as measured by SPI, SPEI_PM, and SPEI_Rn, resulting from CO2 physiological forcing, is projected to increase over 61%, 69%, and 78% of global terrestrial areas, respectively. Notably, we found that the contribution of plant physiological effects (βPHY) to drought characteristics, including intensity, frequency, and duration, exhibits a significant and spatially extensive declining trend with rising CO2 across most land areas. This declining trend is robustly depicted in both the multi‐model mean and individual models. Vegetation coverage plays an important role in the spatial pattern of βPHY. CO2 physiological forcing therefore exerts greater impacts in the tropics, particularly over tropical forests. Our results demonstrate that drought characteristics are expected to become less dependent on plant physiological effects with increasing CO2, a consideration essential for accurate drought projections.